Investigating Posthumanism through the Medium of Self-Representation Using Instagram's Augmented Reality (AR) "Camera Effect" - Muhammad Alzaki Tristi; Nisa Rizkya Andika (Jurnal Komunikasi, 2024)
The Augmented Reality camera effects feature on Instagram provides users with the freedom to create, experiment, and share visual content without limitations, thereby presenting diverse self-images. Remarkably, Indonesia, ranking fourth globally in terms of Instagram users in 2022, demonstrates remarkable adoption of this AR camera effects feature, indicating rapid adoption of new media technology. This research investigates how users engage with this technology to redefine their identities and transcend traditional human boundaries. Through a desk study method, this study analyzes the "Camera Effect" feature on Instagram as a focal point for understanding the phenomenon of self-representation and exploring the concept of posthumanism. By referencing Frank Webster's theory of information society and the posthuman concept in literature, this research reveals that the AR feature on Instagram is a powerful cultural medium for self-representation, overcoming limitations between humans and technology in Indonesian Society. Self-representation becomes pivotal in posthumanism, and AR technology enables exploration and experimentation of diverse identities and expressions. Thus, Instagram's AR technology provides users with new ways to represent themselves, transforming the paradigm of representation and self-identity.